IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH TENTANG PENYELENGGARAAN KETENAGAKERJAAN DALAM PROGRAM BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI KOTA CIMAHI - Tiara Friskadewi (Jurnal Caraka Prabu, 2018)
The research title is "Local Government Policies on Manpower Implementation in the Social Security Administering Body (BPJS) Program in Cimahi City". The research problem is not yet optimistic of the Regional Government Policy on Manpower Implementation in the BPJS Program in Cimahi City, seen from the many workers who have not registered for BPJS in Cimahi City. The identification of the problem of How Local Government Policies on Manpower Implementation in the BPJS Program in Cimahi City. The purpose of this research is to describe and analyze the Local Government Policies on Manpower Implementation in the BPJS Program in Cimahi City. The research method used is descriptive method with a qualitative approach. Data collection techniques through library research and data field studies (observation and interviews). The data analysis technique starts from data reduction, data presentation and at the final stage by drawing conclusions. The sampling technique was done purposively. The results of this study indicate that the implementation of local government policies on the implementation of manpower in Cimahi City has been optimal. This can be seen from the following dimensions; (1) fairly clear policy size and objectives, (2) well-established communication between policy implementers, (3) fairly firm and good characteristics of implementing agencies in managing policy target data, (4) an appropriate socio-economic environment . However, there are some things that are still not optimal. This is because, in terms of the quality of human resources, it is good, but the quantity of existing resources needs to be increased so that the implementation of policies regarding the implementation of manpower in the BPJS program can run more effectively because the quantity of available resources is not comparable to the number of companies in Cimahi City which must be handled Then there is still a lack of accountability and government responsibility towards policy targets, namely the company that feels burdened by the BPJS fees that must be paid for its employees.